2003
DOI: 10.1056/nejmoa020286
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Maintenance Therapy for Vasculitis Associated with Antineutrophil Cytoplasmic Autoantibodies

Abstract: In patients with generalized vasculitis, the withdrawal of cyclophosphamide and the substitution of azathioprine after remission did not increase the rate of relapse. Thus, the duration of exposure to cyclophosphamide may be safely reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
735
7
59

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 1,237 publications
(844 citation statements)
references
References 39 publications
32
735
7
59
Order By: Relevance
“…These protocols were designed to choose an appropriate treatment regimen and to promote prediction of the outcome for each patient. The rates of remission, death, ESRD, and relapse obtained in the trial were comparable to those reported previously in European RCTs [7, 8] with minor differences. Thus, tailor-made treatment based on patients’ disease severity and disease type seemed to be useful in determining treatment regimens.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…These protocols were designed to choose an appropriate treatment regimen and to promote prediction of the outcome for each patient. The rates of remission, death, ESRD, and relapse obtained in the trial were comparable to those reported previously in European RCTs [7, 8] with minor differences. Thus, tailor-made treatment based on patients’ disease severity and disease type seemed to be useful in determining treatment regimens.…”
Section: Discussionsupporting
confidence: 86%
“…Compared with VDI values in the CYCAZAREM trial [7], where the mean VDI (95% confidence interval) values at baseline and at 18 months were 1.3 (1.0–1.6) and 2.5 (2.1–3.0), respectively, those in the present trial were higher by 0.9 and 0.7, respectively.…”
Section: Resultscontrasting
confidence: 68%
See 3 more Smart Citations